PENERAPAN GERAK DASAR MANIPULATIF UNTUK MENINGKATKAN KONSENTRASI ANAK SEKOLAH DASAR - Munthe , Zaskya; Gurning , Nadine Putri; Laia , Hadrian Hadirman; Ginting , Andika Tamari; Sembiring , Heka Maya Sari (ASOSIASI IDEBAHASA KEPRI, 2025)
The focus of this study is to observe the progress in fundamental manipulative movement skills using games for elementary school children. Based on initial observations, it was found that manipulative movement skills based on games can improve children's abilities. The main steps in this research include: (1) conducting research and data collection, (2) development planning, (3) validation, evaluation, and revision by experts, and (4) implementation. Findings from this study indicate that the use of visual media can improve learning outcomes in the manipulative basic motion skills of throwing and catching the ball. From the analysis carried out, it was seen that there was a significant improvement in the learning outcomes of the manipulative basic motion skills of throwing and catching the ball, where all students had met the completeness criteria. The conclusion of this study was that the application of visual media could improve the learning of the basic manipulative motion skills of throwing and catching the ball among elementary school students. Therefore, if children are trained to perform manipulative movements through play, then this will improve their movement skills so that their kinesthetic abilities are in the excellent category. The results obtained from this study created a manipulative system that used the game as its basis.